Dynamic characteristics and microstructural study of nano calcium carbonate modified cemented soil under different salt water solutions. (January 2022) - Chen, Qingsheng; Yan, Ge; Zhuang, Xinshan; Pain, Anindya
Highlights: Nano-CaCO3 for improved strength and corrosion resistance of the cement soil. Dynamic properties of modified cemented soil in different salt water concentrations. SEM and NMR patterns confirms better resistance against sear water corrosion. Empirical relations for small strain elastic modulus and modulus reduction curve of modified cement soil. Abstract: Cemented soil is a cement slurry mixed with soil to form a solidified body, which is usually used in the foundation treatment of large projects such as coastal ports and terminals, airport runways, artificial islands around the sea etc. These infrastructures are commonly exposed to seawater environment, which usually has high corrosive environment and may pose severe deterioration of the cemented foundation. To address these issues, in the present study, nano calcium carbonate (CaCO3 ) is proposed to improve the engineering properties of cement soil. Nano CaCO3 is an ultrafine solid powder material with particle size between 0.01 and 0.1 μm. To verify the improvement effect of nano-CaCO3 on the dynamic properties and corrosion resistance of nano-CaCO3 modified cemented soil, a series of dynamic triaxial tests were conducted on a medium-scale true triaxial apparatus equipped with a cyclic loading device. In addition, nuclear magnetic resonance (NMR) tests and scanning electron microscopy (SEM) tests were conducted to reveal the microstructural mechanism of CaCO3 nanoparticles on the improved cemented soil. The results of the dynamic triaxial tests showed that the small strain elastic modulus of nano-CaCO3 -modified cemented soil increased by 14.3–16.5% compared to the control specimens at the same salt content and cured for 28 days. NMR study confirmed that C-S-H gel grew with nano-CaCO3 at the nucleus, number of small and large pores of the nano-CaCO3 -modified cemented soil were reduced as compared to the controlled specimens. The photographs obtained from the SEM test of the nano-CaCO3 modified cemented soil matches with the pore structure distribution measured by NMR test. The present study provides very conclusive evidence that nano CaCO3 is a very useful ingredient to improve the dynamic characteristics of the clay soil exposed to sea water environment.